Traumatic Injuries of the Upper Extremities in Civilian Victims of Modern Combat Actions - Derkach, R.V.; Yevlantieva, T.А. (TERRA ORTHOPAEDICA, 2025)
Introduction. The increasing number of terrorist attacks and military conflicts targeting civilians has posed a unique challenge to healthcare professionals worldwide. Objective. This study aimed to determine the clinical and nosological structure of upper extremity girdle injuries among civilian victims of modern armed conflicts. Materials and Methods. To carry out our study, we analyzed traumatic injuries to the skeletal bones in 137 civilian patients injured during modern hostilities in Ukraine who were treated in healthcare facilities located in the frontline zone between 2014 and 2023. Results and Discussion. During the full-scale invasion in 2022, a shift was observed in the distribution of upper extremity girdle injuries among civilian victims of modern warfare. The most significant increase was found in patients with hand injuries — their number rose by 7.7 times compared to the pre-war period. A notable increase was also recorded in patients with scapular fractures: while this injury was observed in 1.5% of victims during earlier conflicts, its incidence rose to 8.7% during the full-scale war. In our opinion, this increase resulted from a greater number of mine-explosive injuries affecting a broader segment of the civilian population. The incidence of forearm diaphysis fractures rose more than 2.5 times. An increase was also noted in patients with fractures of the distal forearm, although at a lower rate of 1.4 times. A slight increase was also observed in patients with clavicle fractures. Conclusions. The analysis of the distribution of upper extremity injuries among civilian patients injured in modern armed conflicts revealed significant shifts associated with changes in injury mechanisms, increased intensity of combat operations, and the prevalence of mine-explosive injury during the full-scale invasion.